The Empirical Landscape of Trade Policy - Bown, Chad P.; Crowley, Meredith A (World Bank, Washington, DC, 2016)
This paper surveys empirically the broad features of trade policy in goods for 31 major economies that collectively represented 83 percent of the world's population and 91 percent of the world's GDP in 2013. It addresses the following five questions: Do some countries have more liberal trading regimes than others? Within countries, which industries receive the most import protection? How do trade policies change over time? Do countries discriminate among their trading partners when setting trade policy? Finally, how liberalized is world trade? The analysis documents the extent of cross-sectional heterogeneity in applied commercial policy across countries, their economic sectors, and their trading partners, over time. It concludes that substantial trade policy barriers remain as an important feature of the world economy.